Self-Perceived Impact of Oral Health on the Quality of Life of Women Deprived of Their Liberty - Ludmila Roberto Moraes; Lidiane Castro Duarte de Aquino; Danielle Teles da Cruz; Isabel Cristina Gonçalves Leite (International Journal of Dentistry)
Background. Prison units are marked by structural deficiencies, especially in relation to the female gender. Objectives. To measure the self-perceived impact of oral health on the quality of life of Brazilian women in detention. Methodology. A survey was carried out conducted in the penitentiary at Juiz de Fora (Minas Gerais, Brazil) using an instrument with semistructured questions and validated scales, including the Oral Health Impact Profile-14. 99 women were interviewed. The analysis was based on a theoretical model of determination, with hierarchical blocks of variables. Bivariate analysis was done using the Mann–Whitney, test and multivariate analysis was used using linear regression. The significance level was set at 5%. Results. 33% experienced tooth loss after incarceration, (3.70 ± 3.26 lost teeth). 65.6% rated the dental service as fair/poor. The highest prevalence of oral health impact was for the domains of psychological discomfort (50.5%) and physical pain (40.4%). There is a negative impact on psychological discomfort: the number of dental consultations in the past year and self-perceived general health. There is an impact on physical pain: self-declared color and anxiety. Self-perceived general health had an impact on the domains of psychological disability and social disadvantage. Depression had an impact on the total score. Conclusion. This study revealed a self-perceived impact of oral health on the quality of life of women inmates. We need to ensure high-quality access to dental treatment in prisons.